Micropropagation and shoot regeneration of Cistus creticus ssp. Creticus - Panagiotis Madesis, Elpiniki Konstantinidou, Athanasios Tsaftaris, Irini Nianiou-Obeidat (Journal of Applied Pharmaceutical Science)
Cistus creticus L. ssp. creticus is a medicinal aromatic shrub native in Crete (Greece). The protocol described in this paper provides optimal levels of growth regulators required to obtain high regeneration rates of Cistus in vitro. Micropropagation has been achieved through rapid proliferation of shoot-tips on Murashige and Skoog (MS) basal medium supplemented with 0.2 mg l-1 6-benzylaminopurine (BAP). After four weeks shoots were transferred to MS medium without growth regulators for further development and rooting. The highest percentage of regenerated shoots was obtained with 0.1 mg l-1 TDZ and 0.1 mg l-1 NAA after 4 weeks. Elongation and rooting was readily achieved when multiple shoots more than 1 cm in length were singled out and cultured on the MS medium without growth regulators. The plantlets were successfully adapted and grew vigorously in greenhouse conditions. This is the first report of shoot regeneration in the genus Cistus. The regeneration protocol developed in this study provides a basis for further investigation of the medicinally active constituents of this elite medicinal plant.
Keywords: a-naphthaleneacetic acid (NAA), cretan ladano, shoot regeneration, thidiazuron (TDZ).